Additive-mediated intercalation and surface modification of MXenes. (28th February 2022) - Zou, Jing; Wu, Jing; Wang, Yizhou; Deng, Fengxia; Jiang, Jizhou; Zhang, Yizhou; Liu, Song; Li, Neng; Zhang, Han; Yu, Jiaguo; Zhai, Tianyou; Alshareef, Husam N.
Abstract : The addition of certain additives during intercalation and surface modification can result in MXene-based materials with exceptional performances. Abstract : 2D carbides and nitrides of transition metals, also known as MXenes, are an emerging class of 2D nanomaterials that have shown excellent performances and broad application prospects in the fields of energy storage, catalysis, sensing, electromagnetic shielding, electronics and photonics, and life sciences. This unusual diversity of applications is due to their superior hydrophilicity and conductivity, high carrier concentration, ultra-high volumetric capacitance, rich surface chemistry, and large specific surface area. However, it is difficult to make MXenes with the desired surface functional groups that deliver high reactivity and high stability, because most MXenes are extracted from ceramics (MAX phase) by an etching process, where a large number of metal atoms are inevitably exposed on the surface, with other anions and cations embedded uncontrollably. The exposed metal atoms and implanted ions are thermodynamically unstable and readily react with trace oxygen or oxygen-containing groups to form the corresponding metal oxides or degrade chemically, resulting in a sharp decline in activity and loss of excellent physicochemical properties. The addition of certain synergistic additives during the intercalation and chemical modification of surface functional groups under non-hazardous conditions can result in stable and efficient MXene-based materials with exceptional optical, electrical, and magnetic properties. This review discusses several such methods, mainly additive-mediated intercalation and chemical modification of the surface functional groups of MXene-based materials, followed by their potential applications. Finally, perspectives are given to discuss the future challenges and promising opportunities of this exciting field.